Pelaksanaan Pelayanan Publik di Bidang Pendidikan sebagai Implementasi Kebijakan Otonomi Daerah di Kabupaten Gowa - Sukma, Nur Ichsan; Jayadi, Ahkam (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem of this research is how public services in the field of education in Gowa Regency. The subject matter is then included in several subproblems or research questions, namely: 1) how is the implementation of the public in the field of education as the implementation of regional autonomy policies in Gowa Regency?, 2) What are the factors that affect the performance of the Education Office in implementing public services as the implementation of regional autonomy policies in Gowa Regency?. The results of this study indicate that: 1) Public implementation in the field of Education as the implementation of regional autonomy policies in Gowa Regency is good because the government first designs all programs that will be carried out later. 2) The factors that influence the performance of the Gowa Regency Education Office in carrying out the implementation of regional autonomy are due to several factors including the organizational structure factor and the public service apparatus.